SELEKSI DAN PEROLEHAN GENETIK PADA UJI KETURUNAN NYAWAI (Ficus variegata Blume) DI BANTUL - Liliek Haryjanto; Prastyono Prastyono; Yayan Hadiyan (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2018)
Nyawai (Ficus variegata Blume) is a fast growing species which is promising for forest industrial plantation. Tree improvement of nyawai was then initiated through some progeny trials involving wide range of genetic base in Bantul. Study on initial growth reported that nyawai originated from Cilacap-Pangandaran showed higher genetic variation than those from other locations. However, further growth performance including the effect of selection in the progeny trial was not reported. This study was aimed to observe the growth and genetic parameter of nyawai in the progeny trial at advanced age. The genetic gain resulted from series of within plot selection was also estimated. The design of progeny trial was a randomized complete block with 19 families from Cilacap-Pangandaran, 4 non-contiguous tree-plot, 7 blocks at spacing of 5 m × 5 m. The observed traits were height, diameter at breast height and volume at four years of age. The results of study showed that survival rate was high at 89%. The mean annual increment for height, diameter and volume were 1.52 m/yr; 2.35 cm/yr and 8.65(×10-3) m3/yr, respectively. The proportion of variance to the total variance for family, plot and within plot ranged from 0.06% to 2.10%, 25.54% to 27.50% and 70.57% to 73.91%, respectively. In general, narrow-sense heritability for individual, family and within family were low. Genetic gain from within family selection that was practiced as within plot selection using selection ratio 25% were also low ranging from 0.19% to1.91% for all traits.